DNA Replication Timing, Genome Stability and Cancer - Donley, Nathan (2013)
Normal cellular division requires that the genome be faithfully replicated to ensure that unaltered genomic information is passed from one generation to the next. DNA replication initiates from thousands of origins scattered throughout the genome every cell cycle; however, not all origins initiate replication at the same time. A vast amount of work over the years indicates that different origins along each eukaryotic chromosome are activated in early, middle or late S phase. This temporal control of DNA replication is referred to as the replication-timing program. The replication-timing program represents a very stable epigenetic feature of chromosomes. Recent evidence has indicated that the replication-timing program can influence the spatial distribution of mutagenic events such that certain regions of the genome experience increased spontaneous mutagenesis compared to surrounding regions. This influence has helped shape the genomes of humans and other multicellular organisms and can affect the distribution of mutations in somatic cells. It is also becoming clear that the replication-timing program is deregulated in many disease states, including cancer. Aberrant DNA replication timing is associated with changes in gene expression, changes in epigenetic modifications and an increased frequency of structural rearrangements. Furthermore, certain replication timing changes can directly lead to overt genomic instability and may explain unique mutational signatures that are present in cells that have undergone the recently described processes of “chromothripsis” and “kataegis”. In this review, we will discuss how the normal replication timing program, as well as how alterations to this program, can contribute to the evolution of the genomic landscape in normal and cancerous cells.